Apoptosis Induced by Staphylococcus aureus in Epithelial Cells Utilizes a Mechanism Involving Caspases 8 and 3 - Wesson, Carla A. (American Society for Microbiology, 2000)
In this study, we demonstrate that the mechanism by which Staphylococcus aureus induces apoptosis in bovine mammary epithelial (MAC-T) cells involves caspases 8 and 3, two key components of a proteolytic cascade leading to apoptosis. In addition, internalized S. aureus induces expression of the inflammatory cytokines tumor necrosis factor alpha and interleukin-1β by MAC-T cells. These data suggest that the internalization of S. aureus could induce specific cellular responses in vivo that may ultimately impact the course of infection.